Genetic analysis of pharmacogenomic VIP variants in the Blang population from Yunnan Province of China. Issue 5 (5th April 2019) - Zhang, Chan; Guo, Weiwei; Cheng, Yujing; Li, Qi; Yang, Xin; Dai, Run; Zhu, Linhao; Chen, Wanlu
Abstract: Background: Genetic polymorphisms in numerous pharmacogenetics studies were regarded as the essential factors involved in the response to or metabolism of drugs. These genetic variants called very important pharmacogenetic (VIP) variants played a role in drugs metabolism, which have been summarized in the PharmGKB database. In this study, we genotyped 80 VIP variants from the PharmGKB in 100 members of Blang volunteers from Yunnan province. Methods: Based on the PharmGKB database, we genotyped 80 VIP variants loci located in 47 genes. We used χ 2 tests to evaluate the significant loci between Blang and the other populations, including ASW, CEU, CHB, CHD, GIH, JPT, LWK, MEX, MKK, TSI, and YRI. The global variation distribution of the significant variants was observed from the ALlele FREquency Database. And then, we used F ‐statistics (Fst), genetic structure, and phylogenetic tree analyses to ascertain the genetic affinity among 12 populations. Results: Comparing the Blang with the other 11 populations from the HapMap Project, the statistical results revealed that rs3814055 (NC_000003.12:g.119781188C>T) of nuclear receptor subfamily 1 group I member 2 ( NR1I2, OMIM# 603, 065) was the most significant variant, followed by rs1540339 (NC_000012.12:g.47863543C>T) of vitamin D receptor ( VDR, OMIM#601, 769). Furthermore, we found that genotype frequency of rs3814055 in the Blang was closer to the populations distributed in Miao. And genetic structure and F ‐statistics indicated that the Blangs had a relatively closer affinity with CHD, CHB, and JPT populations. In addition, the Han nationality in Shaanxi was closer to it. Conclusions: Our results will complement the pharmacogenomics information of the Blang ethnic group and provide a theoretical basis for safer drug administration for Blang. Abstract : VIP variants were analyzed in the Blang population. The Blang had a relatively closer affinity with Asian. The results will complement the data of pharmacogenomics about Blang.